Distribution of Student Achievement in Chile : Baseline Analysis for the Evaluation of the Subvención Escolar Preferencial - Murnane, Richard J.; Page, Lindsay; Vegas, Emiliana (World Bank, Washington, DC, 2013)
This paper has two primary objectives. The first objective is to describe our method for predicting the counterfactual outcomes, and explain the reasons for this choice. The second is to present estimates of the counterfactual outcomes. The paper contains the following sections. Section two provides a description of the voucher system before the introduction of SEP (Subvencion Escolar Preferencial program, or Preferential School Subsidy), an explanation of the main components of SEP, and a summary of other educational reforms currently undergoing Parliamentary review, for which SEP may serve as a valuable pilot. In section three, we present the methodological approach employed in this paper to predict the counterfactual outcomes to which actual outcomes under SEP will be compared. Section four describes the data on students and schools used in this paper. This section also provides information on the distributions of grade four priority students and non-priority students among the nation's three types of elementary schools in the years 2005-2007 and predictions of what these distributions will have been in 2008 in the absence of SEP. Section five describes the distributions of achievement of priority students and non-priority students on SIMCE tests of Spanish, mathematics, and natural and social sciences administered at the end of the 2005, 2006, and 2007 school years, and predictions of what the average achievement scores for each group will have been in 2008 had SEP not been introduced. Section six describes trends in achievement gaps between priority and non-priority students and trends in the decomposition of these gaps into within- and between-school differences. Section seven summarizes the key findings from the baseline data analysis. It also describes research agenda for evaluating the initial impacts of SEP on the distribution of schools attended by Priority students and on the achievement of priority students on the SIMCE tests.